2008
DOI: 10.1348/147608308x278295
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behaviour therapy in patients with schizophrenia who are not prescribed antipsychotic medication: A case series

Abstract: CBT is a feasible treatment for people with schizophrenia who are not prescribed antipsychotic medication. It may be a valuable alternative to medication in treating symptoms of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, CBT for psychosis has yet to be formally evaluated in the absence of antipsychotic medication, although there have been a few case studies (Morrison, 1994) that have demonstrated acceptability and provided some support. More recently, two case series have demonstrated some benefits, with four cases of patients experiencing auditory hallucinations showing some gains in terms of symptoms, distress and disability (Morrison, 2001a) and three cases with a diagnosis of schizophrenia showing improvements in positive and negative symptoms (Christodoulides, Dudley, Brown, Turkington, & Beck, 2008).…”
Section: A Critical Analysis Of the Fep Studies: 2 Theoretical Undermentioning
confidence: 99%
“…However, CBT for psychosis has yet to be formally evaluated in the absence of antipsychotic medication, although there have been a few case studies (Morrison, 1994) that have demonstrated acceptability and provided some support. More recently, two case series have demonstrated some benefits, with four cases of patients experiencing auditory hallucinations showing some gains in terms of symptoms, distress and disability (Morrison, 2001a) and three cases with a diagnosis of schizophrenia showing improvements in positive and negative symptoms (Christodoulides, Dudley, Brown, Turkington, & Beck, 2008).…”
Section: A Critical Analysis Of the Fep Studies: 2 Theoretical Undermentioning
confidence: 99%
“…In their meta-analytical evaluation of controlled research and qualitative reviews, Roth and Fonagy [ 19 ] discussed numerous studies with favourable outcomes. CBTp has also been supported with favourable results of case series [ 20 ] and randomised control trials [ 21 ]. An RCT conducted by Tarrier et al [ 22 ] demonstrated that both positive symptoms of psychosis and accompanying emotional distress reduced considerably over the course of CBTp.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive behavioral therapy (CBT) focuses on the relationships between thoughts, beliefs, feelings, and behaviors. Recent meta‐analyses examining the efficacy of CBT in schizophrenia have reported significant improvements in positive and negative symptoms, mood, and functioning (Christodoulides, Dudley, Brown, Turkington, & Beck, ; Grant, Huh, Perivoliotis, Stolar, & Beck, ; Wykes, Steel, Everitt, & Tarrier, ). CBT is now a strongly recommended adjunct to medication treatment of schizophrenia in several national treatment guidelines (e.g., National Collaborating Centre for Mental Health, ).…”
Section: Treatmentmentioning
confidence: 99%